2007
DOI: 10.1016/j.cellbi.2007.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of matrix metalloproteinase‐9 by 4‐methylumbelliferone

Abstract: OHK cells, a human lymphoma cell line, are known to produce large amounts of hyaluronan. We investigated the effect of 4-methylumbelliferone, an inhibitor of hyaluronan synthesis, on the activity of matrix metalloproteinases in OHK cells. Matrix metalloproteinase-9 was detected on gelatin zymography as the main metalloproteinase excreted into the medium of cultured OHK cells, and 4-methylumbelliferone added to the medium decreased the activity of the enzyme in a dose-dependent manner. Addition of Streptomyces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…For example, 4-MU induces the expression of MT1-MMP mRNA, resulting in activation of MMP2 in human skin fibroblasts (67), but in human lymphoma cell lines, 4-MU decreased the level of mRNA for MMP9 (68). In primary human aortic smooth muscle cells 4-MU did not modify the activity of MMP2 but did cause a decrease in cellular migration, migration that could be rescued with the addition of HA (63).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, 4-MU induces the expression of MT1-MMP mRNA, resulting in activation of MMP2 in human skin fibroblasts (67), but in human lymphoma cell lines, 4-MU decreased the level of mRNA for MMP9 (68). In primary human aortic smooth muscle cells 4-MU did not modify the activity of MMP2 but did cause a decrease in cellular migration, migration that could be rescued with the addition of HA (63).…”
Section: Discussionmentioning
confidence: 98%
“…Whether this inhibition was dependent on HA inhibition or a direct effect remains unknown. Nakamura et al (68) reported that 4-MU inhibited MMP9 in a human lymphoma cell line as well as other cultured human carcinoma cells, an inhibition that could not be mimicked by treatment of the cells with hyaluronidase. Given that elevated HA accumulation is often positively correlated with tumor growth and aggressiveness (31,69), it is not surprising that 4-MU would provide inhibitory effects on tumor cell migration, invasion, or cell proliferation by way of blocking HA production.…”
Section: Discussionmentioning
confidence: 99%
“…MMP-9 is produced by neutrophil granulocytes, macrophages, malignant cells and capillary endothelial cells (27). MMP-9 can promote cancer cells to have infiltration invasion through the degradation and destruction of the basilar membrane or new vessels to enhance cancer growth and dissemination (28).…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer in transgenic mice, HA overproduction accelerates tumor angiogenesis through stromal reactions, most notably in the presence of versican [24]. On the other hand, the HAS suppressor, 4-methylumbelliferone (MU), suppresses cell adhesion, locomotion, and matrix metalloproteinase (MMP)-9 and N-cadherin expression, and inhibits tumor metastasis [25][26][27]. HA is composed of high and low molecular weight forms that have been shown to have opposite functions.…”
Section: Hyaluronan and Receptors For Hyaluronan-mediated Motilitymentioning
confidence: 99%